Effects of ICT Integration on English Language Learning at the Secondary Level - Nepal, Shivahari; Paneru, Narendra Raj; Ghimire, Nawaraj (Janajyoti Journal, 2025)
The use of Information and Communication Technology (ICT) in education is receiving growing attention, especially for its ability to make language learning more effective and engaging. The purpose of this study was to explore how ICT effects the teaching of the English Language at the secondary level students. Employing an experimental research design, the study incorporated both pre-test and post-test measures across two groups to evaluate learning outcomes. The study was conducted among 60 ninth-grade students at a public secondary school in Bagmati Municipality, Sarlahi district. From this group, 30 students were chosen for in-depth interviews to gather qualitative insights into their learning experiences. The findings of the study indicated a significant difference in academic performance between the two groups. Specifically, students who were taught using ICT-based methods achieved notably higher results compared to those taught through traditional approaches. These findings highlight the effectiveness of integrating ICT to enhance English Language Learning (ELL) at the secondary school level.